Polycyclic Aromatic Hydrocarbons and their Association with Breast Cancer - León, S Pilar Zamora; López, Fernando Delgado (Bangladesh Journal of Medical Science, 2020)
Background and Rationale: Polycyclic aromatic hydrocarbons are a lipophilic group of pollutants that persist in the atmosphere for long periods, constituting a permanent source of exposure for humans. They have been associated, for a long time, with the risk in developing breast cancer, but there are still unresolved questions. Conclusion: Integrated strategies are required that should consider molecular and population-level studies, to understand and elaborate approaches to prevent the risks in developing breast cancer. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.194-199